Multifunctionality of Russian think tanks in Russian civil society : The limiting effects of the Foreign Agent Law on multifunctionality - Perijäinen, Liisa (fi=Turun yliopisto|en=University of Turku|, 2018)
During the increased NGO-boom and attention towards policy development, think tanks as multifunctional actors of civil society and a special form of independent non-profit and non-governmental organisations greatly contributed to the rebuilding of Russian social sphere after the disintegration of the Soviet Union. However, both Russian social sphere and the organisations representing civil society, for example think tanks, experienced heavy structural changes after the introduction of the Foreign Agent Law in 2012. New amendments within the legislation placed many restrictions and burdens on Russian NGOs, non-profits and think tanks limiting their possibilities to have foreign financing thus affecting their operations and development of Russian civil society in a broader sense. Therefore, the aim of this thesis is to study the role of Russian think tanks and the relations these organisations experience within Russian civil society, taking into consideration the effects of the Foreign Agent Law. The theoretical framework suitable for this study has been drawn from the concepts of societal triangle presented by Tulder and Zwart (2006) as well as the contributions and functions of non-profits in regard to the societal triangle and societal subsystems by Neumayr (2009) and Ivanova and Neumayr (2017). The former allows the examination of a triangular relationship of the society, its societal spheres (the state, market and civil society) included. Further, the latter framework deepens the understanding of the functions performed within the societal triangle with a better focus on civil society sphere and functions performed by the organisations representing civil society. The research has been carried out in the form of the qualitative content analysis, where themes arising from 18 online publications of three selected Russian think tanks have been identified and conceptualised. The thematic elements found in this study have contributed to the understanding of the relations and functions carried out by Russian think tanks as well as their role in Russian civil society including the limitations posed by the Foreign Agent Law since 2012. In harmony with the findings of this study, Russian think tank organisations engage in advocacy and service delivery functions, organisations being clearly market and government driven. Russian think tanks are found to engage in relations with the general public and the government officials but there is a lack of feedback mechanism between the parties. Further, Russian think tanks and other NGOs are found to be operating within a monocentric regime, where Russian government and security officials use power as a demonstrative tool in order to achieve the desired results. The new law design (the Foreign Agent Law) is of strategic value to the government officials but is contradictory and discriminatory when viewed from the think tank perspective.